Pengembangan Sistem Aplikasi Barbershop Berbasis Android Untuk Menumbuh Kembangkan Usaha Barbershop - Hariman Bahtiar; Huswatun Mahmudah; Yupi Kuspandi Putra; Fathurahman Fathurahman (Infotek: Jurnal Informatika dan Teknologi, 2022)
The development of communication and information technology is one of the developments that can be felt in everyday life. The development of smartphones or smartphones and the internet is one of the real evidences. Another development that has felt its impact is the development of fashion. Nowadays fashion is no longer synonymous with women, but also for men. Not only fashion clothes or accessories, but also hair fashion. More and more hairstyles are becoming more and more confusing for consumers to choose the type of hairstyle they want. Many men also do not know the details obtained from other people about the new hairstyle. Therefore, the development of this Barbershop application can also help choose the desired hairstyle and can assist application users in making their choice. In addition, the application can determine the location of the nearest or best Barbershop for its users. Based on the conclusions of the results of this study, the application of barbershop services at Barbershops is useful for facilitating information problems and ordering barber services without customers having to come to the Barbershop and being able to create a good system that can facilitate employee performance at the Barbershop itself